Exploring sharing behaviors across social media platforms. (March 2019) - Ham, Chang-Dae; Lee, Joonghwa; Hayes, Jameson L; Bae, Young Han
Increasingly, consumers are simulcasting branded content across multiple, interconnected social media platforms creating a complex social media ecosystem. However, little is known about what motivates sharing in the ecosystem as opposed to specific media contexts. Present research explores multiplatform consumers' general sharing motivations and examines how those motivations, in conjunction with social relationships, influence sharing behavior across social media platforms. First, four focus group interviews were conducted to identify general social media sharing motivations of multiplatform consumers. Employing an online survey ( N = 249), four dimensions comprised of 31 sharing motivation items were identified: social presence, social conversation, easy connection, and self-management . Applying a theory of reasoned action and social exchange theory approach, we conducted a second online survey ( N = 342) to elaborate on our findings in terms of multidimensionality and interdependency among the influencing factors on social sharing behavior. Social conversation exhibited the strongest relationship with attitude toward sharing, whereas self-management was negatively related to the social norm, which, in turn, was negatively associated with sharing intention. Findings and implications are discussed.